RANCANG BANGUN SISTEM PEMANTAUAN APLIKASI DAN KLASIFIKASI KONDISI MENGGUNAKAN METODE ANFIS UNTUK PASIEN STROKE RINGAN - I Made Ananta Wiragunawan; n/a Nurussa’adah; Thareq Barasabha (Jurnal Mahasiswa TEUB, 2023)
Stroke is an acute clinical event of focal or global neurological disorders associated with cerebral circulation disorders. A stroke usually lasts more than 24 hours and can lead to death with no known cause. Stroke is a disease in which blood cannot flow to the brain to supply oxygen and nutrients and cannot get rid of waste products. This causes brain cells to rapidly die. The success of stroke treatment management is very dependent on time. The sooner the first aid is given, the better the clinical outcome will be. Through these problems, technology is needed that can monitor the condition of stroke patients on a regular basis. The technology needed is primarily able to monitor several risk factors for stroke, namely blood pressure, cholesterol, pulse, and blood sugar using Photoplethysmograph (PPG) sensors and provide education in reducing these risk factors. This innovation has tested the function of the tool by measuring blood pressure, cholesterol, pulse, and blood sugar levels using an innovative tool compared to the results of laboratory measurements. The results of the measurement of innovation tools with blood pressure measurement accuracy of 95,78%, total cholesterol measurement accuracy of 96,88%, and blood sugar level measurement accuracy of 96,49%. Result of the monitoring application supported by the ANFIS system, the results of the classification of user conditions were obtained with an accuracy rate of 95 % in testing five patients who had high risk factors for stroke. Keywords: Stroke, Photoplethysmograph, Monitoring Application, ANFIS, Therapy DAFTAR PUSTAKA[1] Setyopranoto, I., Bayuangga, H.F., Panggabean, A.S., Alifaningdyah, S., Lazuardi, L., Dewi, F.S.T., Malueka, R.G., 2019. Prevalence of stroke and associated risk factors in sleman district of Yogyakarta Special Region, Indonesia. Stroke Res. Treat. 2019. https://doi.org/10.1155/2019/2642458[2] Powers, W.J., Rabinstein, A.A., Ackerson, T., Adeoye, O.M., Bambakidis, N.C., Becker, K., Biller, J., Brown, M., Demaerschalk, B.M., Hoh, B., Jauch, E.C., Kidwell, C.S., LeslieMazwi, T.M., Ovbiagele, B., Scott, P.A., Sheth, K.N., Southerland, A.M., Summers, D. V., Tirschwell, D.L., 2018. 2018 Guidelines for the Early Management of Patients With Acute Ischemic Stroke: A Guideline for Healthcare Professionals From the American Heart Association/American Stroke Association, Stroke. https://doi.org/10.1161/STR.0000000000000158 [3] Kemenkes RI, 2018. Hasil Riset Kesehatan Dasar Tahun 2018. Kementrian Kesehat. RI 53, 1689–1699.[4] Salvadori, E., Papi, G., Insalata, G., Rinnoci, V., Donnini, I., Martini, M., Falsini, C., Hakiki, B., Romoli, A., Barbato, C., Polcaro, P., Casamorata, F., Macchi, C., Cecchi, F., Poggesi, A., 2021. Comparison between ischemic and hemorrhagic strokes in functionaloutcome at discharge from an intensive rehabilitation hospital. Diagnostics 11. https://doi.org/10.3390/diagnostics11010038[5] Umar, U., Amin, I., Elektro-Medis, T., Kesehatan, P., & Makassar, M. (2019). Monitoring Kadar Glukosa Darah NonInvasif Menggunakan Sensor Photoacoutic. In Celebes Health Journal (Vol. 1, Issue 2). http://journal.lldikti9.id/CPHJ/indexDOI:https://doi.org/